The Effect of Using Crossword Puzzle Model on Learning Interest in Indonesian Learning Based on Students' Literacy - Muhammad Khaedar; Syamsul Alam (Jurnal Pendidikan dan Pengajaran, 2023)
Learning Model requires coaching and developing students' thinking skills, especially in the cognitive domain to combine playing with learning. Students are engaged in learning using the crossword puzzle method, both mentally and physically. The purpose of this study is to analyze the impact of the crossword puzzle model on students' interest to learn Indonesian based on how well students can read. This study employed a quasi-experimental experimental design. All 35 samples of third-grade pupils served as the study's subjects. Data collection techniques are observation, questionnaire and test and documentation. The data analysis techniques used is descriptive data analysis. According to research findings, adopting the crossword puzzle approach had an impact on students' enthusiasm in learning Indonesian based on literacy. Students' interest in learning Indonesian using crossword puzzle media was higher with an average score of 91.55 if compared with the control class that did not use crossword puzzle media, which was 64.23. It can be concluded that there is a significant effect of crossword puzzle media on students' interest in learning Indonesian. The implication of this study is in available for elementary schools in implementing learning with crossword puzzles, carried out and adapted to the abilities and conditions of students.